TUAN GURU HAJI NAJMUL AKHYAR'S ISLAMIC SPIRITUAL EMPOWERMENT TOWARDS THE COMMUNITY OF NORTH LOMBOK - Madeni; Usman (Jurnal Da'wah: Risalah Merintis, Da'wah Melanjutkan, 2023)
This research discusses the process of spiritually based community empowerment by Tuan Guru H. Najmul Akhyar towards the people of Menggala Hamlet, North Lombok using qualitative methods. This research results in the conclusion that Tuan Guru H. Najmul Akhyar empowers the community using three community empowerment strategies, namelyrelief and welfare which is aimed at the community to provide education to the community, such as providing housing assistance to the community, establishing Islamic boarding schoolscommunity development which aims to reach out to people who have not been able to afford it, to approach the community, to conduct ummahat studies.empowering people which aims to provide skills training, among skills.